TINJAUAN KESEDIAAN AIR BERSIH IBUKOTA KECAMATAN SUWAWA KABUPATEN BONE BOLANGO - Nusu, Olgha; Maulidiyah, Yesi (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2013)
ABSTRAK Suwawa capital district, located in the district of Bone Bolango. Geographically located at 0o 19 '55 "- 0o 47' 48" N and 123o 3 '44 "- 123o 31' 37" East Longitude. This district in the east by Gorontalo city, west of the border with Suwawa district, northern district bordering Kabila and the south by District Tapa. Ulanta Village, Village Bube, Bulodawa village has an area of ​​18.21 km2 or equal to 21.106% of the total district population Suwawa with 4408 inhabitants in the year 2011 based on data from BPS Bone Bolango water source for the villages in the district is taken from the river Ulanta. In calculating population projections using the Arithmetic and Geometric methods and followed by calculation of water requirements using the criteria of the Directorate General of Human Settlements planning Public Works Department, 1996. From the calculation of the normal water demand in 2015 (5-year projection) in the village of Ulanta, Bube village, and the village Bulodawa amounted to 0.075 m3, while the maximum water demand is equal to 0.086 m3 and water demand at peak hours obtained for 0.131 m3/second. Analysis of the water demand associated with the availability of water in an average Ulanta River is considered constant since 2009 through 2015 amounted to 0.616 m3, the availability of water is sufficient to meet the needs of normal water and required maximum water demand is 0.075 m3 <0.616 m3 and 0.086 m3 <0.616 m3. While the peak hour water demand with the availability of sufficient water is 0.131 m3> 0.616 m3. Keywords : Domestic and Non Domestic Needs